identificación Y Frecuencia De Hemoparásitos Encontrados En Palomas (Columba Livia) Provenientes De La Plaza De Bolívar, Bogotá D.C. - Colombia (2021)
The pigeons share common spaces with the human being in which they reproduce in great densities to levels of calling them plague, in these spaces there is a great health risk to man (Méndez, Villamil, Buitrago & Soler, 2013). Pigeons are part of the Columbiformes family and are domestic species. that have managed to adapt to adverse conditions in different parts of the world, including Columbia. In the country this species has colonized places common to other species of animals and even humans such as parks, churches, restaurants, schools and water fountains in main squares (Pérez, Monsalve & Márquez, 2015). These animals have been transmitters of zoonotic diseases both for humans as for animals, they are vectors of different types of pathogens and parasites through their feathers and fecal matter without taking into account the damage to buildings (Bernal, Rivas, Rodriguez, Vasquez & Velez, 2011).